Analisis Gaya Kepemimpinan Kepala Sekolah serta Lingkungan Kerja dalam relasi Tenaga Pendidik dan Stake Holder - Luis Andrew Abraham A; Martinus Rehan (STKIP PGRI SITUBONDO, 2022)
The principal holds the authority to govern the school effectively in order to accomplish the school’s objectives. The principal’s leadership style is determined by the outcomes of their capacity to influence one another, and they must be able to collaborate on actions to accomplish goals. A positive and pleasant work environment in which educators and stakeholders interact is necessary to increase passion for learning activities, which will result in increased abilities and the production of the desired quality. This study employs a qualitative approach, a descriptive research method that relies heavily on the researcher as the primary instrument. The data analysis was performed inductively and descriptively. Additionally, this study places a priority on methods over outcomes. The principal’s implementation of the appropriate leadership style affects the quality of educators’ competence, resulting in increased stakeholder satisfaction due to an increase in the quality of excellent graduates. Principals must be enthusiastic about educators and stakeholders to foster a positive work environment conducive to school performance.